Locus of Control and Self-Esteem as Predictors of Maternal and Child Healthcare Services Utilization in Nigeria - Aikpitanyi, Josephine; Okonofua, Friday; Ntoimo, Lorretta; Tubeuf, Sandy (Frontiers in Health Services, 2022)
This study investigated the influence of locus of control and self-esteem on the utilization of maternal and child healthcare services in Nigeria. Specifically, it explored the differences in utilization of antenatal care, skilled birth care, postnatal care, and child vaccination by women having an internal and external locus of control and women having high and low self-esteem. It also examined the association between utilization of maternal and child healthcare on other sociodemographic characteristics. We collected information on non-cognitive traits of 1411 randomly selected women along with information on utilization of various indicators of maternal and child healthcare services. We estimated logistic regression models for various components of maternal and child healthcare services utilization and found that women’s internal locus of control was a significant predictor of utilization of antenatal care, skilled birth care and completion of child vaccination. We also found that having a high self-esteem was a significant predictor of utilization of antenatal care, postnatal care and completion of child vaccination after adjusting for other control variables. By improving our understanding of non-cognitive traits as possible barriers to maternal and child healthcare utilization, our findings offer important insights for enhancing participants’ engagement in intervention programs that are initiated to improve maternal and child health outcomes in lower-middle-income countries.